Decolonizing Queer time: a critique of anachronism in latin@ writings - Eliana de Souza Avila (Ilha do Desterro)
While the term Latin@ is untraceable to any coherent referent in terms of geographical or epistemic origin (Rodríguez 2014), still it denotes a very stable referent when it comes to geographical destination — the USA being the central migratory destiny shaped by and shaping identity shifts and epistemic positions variously associated with Latin America. As much as this narrative determinacy is the effect of global power asymmetries, it also tends to naturalize them by couching migration in evolutionist terms that anachronize struggles against displacement, deterritorialization, and dispossession. The field of Latin@ literature and criticism therefore becomes an effective locus from which the ongoing historical conflicts elided by those narratives can be creatively recalled and reconfigured. This essay reflects on the temporal borderlands as a critical paradigm for reconfiguring narratives of straight temporality within Latin@ texts.